The Winning Cars of the Indianapolis 500 - Reinhardt, James Craig (Red Lightning Books, 2019)
Featuring nearly 200 images of the automobiles and individuals who make the race renowned, this book showcases the top drivers and how racing has changed through two world wars, the Great Depression, and unforgettable accidents.